THE IMPACT OF FEAR OF MISSING OUT ON OBSESSIVE-COMPULSIVE BUYING BEHAVIOR: EXPLORING THE ROLE OF BRAND PASSION (AMONG GENERATION Z IN PEKANBARU CITY) - Iqbal, Mohamad; Afwa, Awliya; Moniko, Moniko (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study examines the influence of Fear of Missing Out (FoMO) on obsessive-compulsive buying behavior among Generation Z in Pekanbaru City. It also analyzes the mediating roles of harmonious brand passion and obsessive brand passion in this relationship. Using a quantitative approach with 200 participants, the findings reveal that FoMO and obsessive brand passion directly affect obsessive-compulsive buying. Additionally, FoMO directly influences both harmonious and obsessive brand passion. However, harmonious brand passion does not have a direct effect on obsessive-compulsive buying and does not mediate the relationship between FoMO and obsessive-compulsive buying. In contrast, obsessive brand passion serves as a mediator in the relationship between FoMO and obsessive-compulsive buying. These findings highlight the critical role of psychological factors and brand passion in shaping consumer behavior, providing valuable insights for marketers and policymakers to mitigate excessive consumption among younger generations. Keywords: Fear of Missing Out (FoMO), Harmonious Brand Passion, Obsessive Brand Passion, Obsessive-Compulsive Buying